Factors influencing bathymetric distribution of benthos in Gobindsagar reservoir, Himachal Pradesh - Koushal, D K; Prakash, A (Indian Journal of Fisheries, 2011)
Factors influencing the bathymetric distribution of macro-invertebrates were determined in Gobindsagar, an impoundment across the river Sutlej, from July 1981 to June 1983. The largest populations of 2,986 n m2 were found in the deepest part of the reservoir. The relative contributions of chironomids to total biomass decreased with increasing depths; the reverse was true for oligochaetes. The strong development of benthos in profundal zone was attributed to a consistently greater organic content of sediment and to the wide fluctuations in water levels